Tata Kelola, Tekanan Luar, Dan Kinerja Keuangan terhadap Integritas Laporan Keuangan (Corporate Governance, External Pressure, and Financial Performance on Integrity of Financial Statements) - Nizam, Fahrul; Nur, Emrinaldi; Supriono, Supriono (STIE Malangkucecwara, 2022)
This study aims to analyze the effect of good corporate governance, external pressure and financial performance on the integrity of financial statements. Empirical study on manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. Using 75 samples of companies with the selection using purposive sampling. Using the SPSS program to test the data analysis, namely multiple linear regression and classical assumption test. The results of the study indicate that audit tenure and leverage have no effect on the integrity of financial statements. Institutional ownership, independent commissioners, audit committees, and profitability have a significant effect on the integrity of financial statements.